Electrochemical Evaluation of Selenium (IV) Removal from Its Aqueous Solutions by Unmodified and Modified Graphene Oxide - Koudelkova, Zuzana; Bytesnikova, Zuzana; Xhaxhiu, Kledi; Kremplova, Monika; Hynek, David; Adam, Vojtech; Richtera, Lukas (Molecules, 2019)
The removal of selenium from superficial and waste water is a worldwide problem. The maximum limit according to the World Health Organization (WHO) for the selenium in the water is set at a concentration of 10 μg/L. Carbon based adsorbents have attracted much attention and recently demonstrated promising performance in removal of selenium. In this work, several materials (iron oxide based microparticles and graphene oxides materials) and their composites were prepared to remove Se(IV) from water. The graphene oxides were prepared according to the simplified Hummer's method. In addition, the effect of pH, contact time and initial Se(IV) concentration was tested. An electrochemical method such as the differential pulse cathodic stripping voltammetry was used to determine the residual selenium concentration. From the experimental data, Langmuir adsorption model was used to calculate the maximum adsorption capacity. Graphene oxide particles modified by iron oxide based microparticles was the most promising material for the removal of Se(IV) from its aqueous solution at pH 2.0. Its adsorption efficiency reached more than 90% for a solution with given Se(IV) concentration, meanwhile its maximal recorded adsorption capacity was 18.69 mg/g.
Keywords: adsorpce; Microspheres; Static Electricity; chemické látky znečišťující vodu; Hydrogen-Ion Concentration; Adsorption; elektrochemické techniky; teplota; koncentrace vodíkových iontů; Time Factors; mikrosféry; časové faktory; Selenium; Temperature; statická elektřina; grafit; selen; velikost částic; Particle Size; Solutions; Electrodes; roztoky; Electrochemical Techniques; Water Pollutants, Chemical; Graphite; elektrody